2015
DOI: 10.1002/jcp.24910
|View full text |Cite
|
Sign up to set email alerts
|

miR-1470 mediates lapatinib induced p27 upregulation by targeting c-jun

Abstract: Our previous study indicated that lapatinib induces p27-dependent G(1) arrest through both transcriptional and post-translational mechanisms. Using miRNA microarray technology and quantitative RT-PCR, we further investigated the potential miRNAs that involved in p27 upregulation and Her-2 signaling pathway alteration with lapatinib treatment. A subset of 7 miRNAs was significantly affected in both 0.5 µM and 2.0 µM and 24 h and 48 h lapatinib treatment. Among them, only miR-1470, miR-126, and miR-1208 were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…We observed that overexpressed c-Jun in TRIM62 overexpression CC cells resulted in up-regulated CyclinD1 expression and down-regulated P27 expression. It is reported that c-Jun was able to activate the promoter of cyclinD1 [34], and CyclinD1 could act as a negative regulator of P27 [40]. So we speculated c-Jun might up-regulate CyclinD1 expression by activating its promoter, consequently down-regulating P27 expression.…”
Section: Discussionmentioning
confidence: 89%
“…We observed that overexpressed c-Jun in TRIM62 overexpression CC cells resulted in up-regulated CyclinD1 expression and down-regulated P27 expression. It is reported that c-Jun was able to activate the promoter of cyclinD1 [34], and CyclinD1 could act as a negative regulator of P27 [40]. So we speculated c-Jun might up-regulate CyclinD1 expression by activating its promoter, consequently down-regulating P27 expression.…”
Section: Discussionmentioning
confidence: 89%
“…MicroRNAs (miRNAs) play crucial roles in regulating cancer biology, including proliferation, apoptosis, and drug resistance 19 . Our previous studies have identified several miRNAs associated with the sensitivity of breast cancer to multiple drugs, including tamoxifen 20 , olaparib 21 , saracatinib 22 , and lapatinib 23 . To investigate whether miRNAs were associated with palbociclib sensitivity, we used microarray to establish differential miRNA expression profiles between palbociclib-sensitive cells and palbociclib-insensitive cells after palbociclib treatment.…”
Section: Resultsmentioning
confidence: 99%
“…All six candidate miRNAs that we identified had ID names higher than 1,000, indicating that they were discovered relatively recently. Therefore, there are only a few reports describing the mechanisms through which these miRNAs are involved in various cancers or chronic diseases that cause cancers (see Supplementary Table S4) 6269 . We could predict a total 884 target genes of six candidate miRNAs by TargetScan Human 7.2 software and Mirtarbase database.…”
Section: Discussionmentioning
confidence: 99%